2020
DOI: 10.2319/052719-362.1
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic perception of facial profile changes in Class II patients treated with Herbst or Forsus appliances

Abstract: Objective To evaluate the esthetic perceptions of orthodontists and laypersons for facial profile changes after orthodontic treatment using Herbst or Forsus appliances. Materials and Methods Pre- and posttreatment facial profile contour images of 20 Class II patients treated with Herbst (group H; n = 10) and Forsus (group F; n = 10) appliances were analyzed by 30 orthodontists and 30 laypersons, who graded them from 1 (unattr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…In both studies 18,19 results are similar to ours: Class II Treatment had positive effect in both cases.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In both studies 18,19 results are similar to ours: Class II Treatment had positive effect in both cases.…”
Section: Discussionsupporting
confidence: 86%
“…Moresca et al 18 focused on Class II malocclusion treatment using the Herbst appliance, concluding that may produce a more esthetically improved facial profile silhouette compared with the one using the Forsus appliance. Our results did not compare skeletal but only dentoalveolar advancement devices, though.…”
Section: Discussionmentioning
confidence: 99%
“…Recent researches have indicated that orthodontic treatment with functional appliances is associated with increased facial profile attractiveness, 20 , 26 , 27 and that functional treatment should be considered as a treatment option to improve the facial appearance of Class II subjects. 26 Besides, Class II treatment with the Herbst appliance may produce a more esthetically improved facial profile silhouette when compared to the Forsus ® appliance, but the changes perceived by evaluators may not be considered clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,[12][13][14] Herbst tedavisi sonucunda oluşan iskeletsel ve dişsel değişimler, yumuşak dokuları da etkilemektedir ve tedavi sonrasında hastaların profilinde iyileşme olduğu bildirilmektedir. 15,16 Temel olarak, Herbst apareyi ile başarılı bir tedavi için, maksiller ve mandibular dişlerin iyi hizalanması ve diş pozisyonlarının özellikle sagittal yönde normal pozisyonda olması istenmektedir. Hareketli fonksiyonel ortopedik apareylerin aksine, Herbst apareyinin avantajları aşağıda belirtildiği şekilde özetlenmektedir: 6 1-Herbst apareyi dişlere sabitlendiği için hastadan herhangi bir yardım almadan günde 24 saat kesintisiz çalışır.…”
Section: Introductionunclassified